2019
DOI: 10.1111/jdv.15671
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and pregnancy outcomes in biological therapies: a real‐life, multi‐centre experience

Abstract: four of them) or by RCM alone (evaluation performed by six of them) 1 year before and results were compared with the previous study. Mean sensitivity, specificity and overall diagnostic accuracy (ACC) and 95% CI were calculated for the specific diagnosis of different facial lesions (Table 1). As expected, considering the evaluation of the seven experts, the combination dermoscopy/RCM had a higher mean ACC for both malignant tumour (including LM/LMM) and LM/LMM of the face (84%, CI 80-89 and 84%, CI 79-89, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 16 publications
0
28
0
6
Order By: Relevance
“…To conclude, biotechnological therapies seem to be safe 10,11,38 and, in selected circumstances, their use should be considered even in the case of previous malignancies 16 …”
Section: Surgical Proceduresmentioning
confidence: 99%
“…To conclude, biotechnological therapies seem to be safe 10,11,38 and, in selected circumstances, their use should be considered even in the case of previous malignancies 16 …”
Section: Surgical Proceduresmentioning
confidence: 99%
“…However, the authors stated that the diverse fi ndings across disease groups in this study may indicate an association related to the underlying disease activity rather than to agent-specifi c effects [71]. As a general approach, it is recommended that women using anti-TNF- avoid pregnancy and be monitored if they have already become pregnant, but there is no conclusive evidence that adalimumab, infl iximab, etanercept and certolizumab pegol treatments are embryotoxic or teratogenic [59][60][61]. Therefore, it has been reported that the continuation of the treatment according to the risk-benefi t balance should be decided individually in each patient.…”
Section: Pregnancy Course In Patients With Psoriasismentioning
confidence: 87%
“…In these periods, the most appropriate treatment after topical agents is broadband or especially narrow band that these anomalies may be biased because they actually refl ect negative outcomes collected by the FDA [66,67]. Data on the safety of anti-TNF- treatments during pregnancy are increasing gradually [59][60][61]. Since these treatments are mostly used in infl ammatory bowel diseases and rheumatoid arthritis, most of the data have been obtained from the literature of gastroenterology and rheumatology [68,69].…”
Section: Pregnancy Course In Patients With Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been observed that when Th17 activity increases above Treg, complications arise, such as preterm labor, preeclampsia, and spontaneous abortions in patients diagnosed with inflammatory diseases such as systemic lupus erythematosus, rheumatoid arthritis, and multiple sclerosis (Figueiredo & Schumacher, 2016). By extrapolation one can infer that psoriasis in itself is a condition that overshadows pregnancy, as its severity is directly related to complications, according to Yang et al, Johansen et al, Odorici et al, and Bröms et al, it can cause spontaneous abortions, preterm labor, and restricted intrauterine growth (Bröms, Haerskjold, Granath, et al, 2018;Figueiredo & Schumacher, 2016;Johansen, Jimenez-Solem, Haerskjold, Sand, & Thomsen, 2018;Odorici et al, 2019;Yang, Chen, Chen, & Lin, 2011).…”
Section: Discussionmentioning
confidence: 99%